Emerging treatments of dementia - Qadir, MI; T-ul-Nisa, A Zafar (Journal of College of Medical Sciences-Nepal, 2012)
DOI: http://dx.doi.org/10.3126/jcmsn.v7i3.6712 Journal of College of Medical Sciences-Nepal, 2011, Vol-7, No-3, 56-61